P490 A vedolizumab population pharmacokinetic model including intravenous and subcutaneous formulations for patients with ulcerative colitis. (25th January 2019) - Rosario, M; Polhamus, D; Chen, C; Sun, W; Dirks, N
Abstract: Background: Vedolizumab is a gut-selective, humanised, monoclonal α4β7 integrin antibody approved as an intravenous (IV) formulation to treat adult patients with moderately to severely active ulcerative colitis (UC). A population pharmacokinetic (PK) model was previously developed for vedolizumab IV. [1] Here we present an update of that model to include data for the investigational vedolizumab subcutaneous (SC) formulation. Methods: The population PK analysis included data from 4 vedolizumab clinical studies: VISIBLE 1 (NCT02611830), GEMINI 1 (NCT00783718), GEMINI 2 (NCT00783692), and VISIBLE open-label extension (NCT02620046). The methods for this population PK model were reported previously. 1 In brief, the structural PK model was described by a 2-compartment model with parallel linear and nonlinear elimination. 1 The model-predicted vedolizumab concentrations were compared across different SC and IV regimens. Results: The impact of covariates on vedolizumab clearance was similar to that described previously; the only predictors with the potential to be clinically meaningful (effect sizes greater than ± 25%) were body weight and albumin at extreme values. 1 The predicted median (90% confidence interval [CI]) average vedolizumab concentration (Cavg ) at steady-state from VISIBLE 1 was 39.7 µg/ml (20.8–75.2) for the vedolizumab SC Q2W arm (Figure 1). The predicted Cavg for the IV Q8W arm [32.2 µg/ml (90% CI, 16.6–60.6)] was similar to SC Q2W and lower than IV every 4 weeks (Q4W) [59.6 µg/ml (90% CI, 31.4–113.0)] predicted from the GEMINI 1 study (Figure 1). Conclusions: Vedolizumab SC (108 mg) administered Q2W produces average drug serum concentrations similar to those for vedolizumab IV (300 mg) Q8W and lower than those for vedolizumab IV (300 mg) Q4W. Reference 1. Rosario M, Dirks NL, Gastonguay MR, et al . Population pharmacokinetics-pharmacodynamics of vedolizumab in patients with ulcerative colitis and Crohn's disease. Aliment Pharmacol Ther 2015;42:188–202